(untitled) (Scientific journal of the Fergana State University, 2024)
The article reveals the inextricable connection of social memory with cultural values in the social structure of society, the influence and significance of social changes in public life on the development of social memory. the influence of its place on national social memory, the processes of formation and development of social memory are revealed. Also important factors in ensuring and developing social memory and harmony of values in society and paradigmatic changes in society is the importance of views aimed at individual social groups or the entire society instead of traditional approaches to national social memory in the context of Globalization has been explored.